A Study on Knowledge, Attitude and Practice in Preventing Transmission of Scabies in Pesantren Darul Fatwa, Jatinangor - Mahirah Binti Mohd Yusof; Silvita Fitri; Yunita Damopolii (Althea Medical Journal, 2015)
Background: Scabies is caused by infestation and sensitization of Sarcoptess cabiei and is an endemic in tropical and subtropical regions around the world. Several factors in the disease transmission are overcrowded living conditions, poor personal hygiene, unhealthy behaviors and population density. Pesantren is a spesific name for an educational Islamic institution in Indonesia and which w could be one of the risk factors of the transmission the disease. Most of the students (santri) are staying at the institution for a long time. The objective of this study was to know the level of knowledge, attitude and practice of santri in preventing scabies.Methods: A descriptive study was conducted on 45 santri in Pesantren Darul Fatwa in Jatinangor during September–December 2012. A questionnaire was set up consisting of questions about age, sex, basic knowledge, attitude, and practice of preventing the transmission of scabies. Data were analyzed using frequency distribution.Results: The level of knowledge and attitude of the respondents to prevent the transmission of scabies were good, meanwhile the level of practice was moderate. There were still questions that could not be answer by the respondents those were the etiology (31.1%), the cut off chain of transmission (40%), and how to prevent scabies (37.8%). Not washing the towel, changing the bed linen and pillow case every 2 weeks were the less good practice performed by the respondents.Conclusions: The knowledge and attitude towards the prevention of transmission of scabies are good while the practices are moderate. A further study with more sample size should be carried out including enviromental assessment.Keywords: Attitude, knowledge, practice, scabiesDOI: 10.15850/amj.v2n1.448